An optical study of drug resistance detection in endometrial cancer cells by dynamic and quantitative phase imaging. Issue 7 (2nd April 2019) - Yao, Tian; Cao, Runyu; Xiao, Wen; Pan, Feng; Li, Xiaoping
Abstract : Platinum chemosensitivity detection plays a vital role during endometrial cancer treatment because chemotherapy responses have profound influences on patient's prognosis. Although several methods can be used to detect drug resistance characteristics, studies on detecting drug sensitivity based on dynamic and quantitative phase imaging of cancer cells are rare. In this study, digital holographic microscopy was applied to distinguish drug‐resistant and nondrug‐resistant endometrial cancer cells. Based on the reconstructed phase images, temporal evolutions of cell height (CH), cell projected area (CPA) and cell volume were quantitatively measured. The results show that change rates of CH and CPA were significantly different between drug‐resistant and nondrug‐resistant endometrial cancer cells. Furthermore, the results demonstrate that morphological characteristics have the potential to be utilized to distinguish the drug sensitivity of endometrial cancer cells, and it may provide new perspectives to establish optical methods to detect drug sensitivity and guide chemotherapy in endometrial cancer. Abstract : Drug resistance detection is crucial for cancer treatment. This research aims at revealing relations between drug resistance of cancer cell and cellular morphology. The morphological changing process of drug‐resistant and nondrug‐resistant endometrial cancer cell are measured by digital holographic microscopy and results show that cells with different degree of drug resistance have distinct morphological changes exposing to cisplatin. The research may provide new perspective to guide drug resistance detection.